Flooded Through the Back Door: The Role of Bank Capital in Local Shock Spillovers - Rehbein, Oliver; Ongena, Steven (Journal of Financial and Quantitative Analysis, 2022)
Abstract This article demonstrates that low bank capital carries a negative externality because it amplifies local shock spillovers. We exploit a natural disaster that is transmitted to firms in nondisaster areas via their banks. Firms connected to a strongly disaster-exposed bank with lowest-quartile capitalization significantly reduce their total borrowing by 6.6% and tangible assets by 6.9% compared to similar firms connected to a well-capitalized bank. These findings translate to negative regional effects on GDP and unemployment. Additionally, following a disaster event, banks reduce their exposure to currently unaffected but generally disaster-prone areas.